The Influence of Work Discipline and Work Environment on Employee Performance Through Work Motivation at the Pratama Jakarta Setiabudi Satu Tax Office - Roy Yan Morgana; Iwan Kurniawan Subagja (Journal of Islamic Studies & Social Science, 2024)
This study aims to: 1) determine the effect of work discipline on employee performance, 2) determine the effect of the work environment on employee performance, 3) determine the effect of work discipline on work motivation, 4) determine the effect of the work environment on work motivation, 5) determine the effect of work motivation on employee performance, 6) determine the effect of work discipline on employee performance through work motivation, and 7) determine the effect of the work environment on employee performance through work motivation. The study was conducted at the Pratama Jakarta Setiabudi Satu Tax Office with a research sample of 81 respondents. The sampling technique used simple random sampling. The data analysis method used descriptive analysis and path analysis. The results of the study indicate that: 1) there is an influence of work discipline on employee performance, 2) there is an influence of the work environment on employee performance, 3) there is an influence of work discipline on employee performance, 4) there is an influence of the work environment on employee performance, 5) there is an influence of work motivation on employee performance, 6) there is no influence of work discipline on employee performance through work motivation, and 7) there is no influence of the work environment on employee performance through work motivation. The work motivation variable cannot mediate the work discipline and work environment variables on improving employee performance